Penerapan model pembelajaran window shopping materi vektor untuk meningkatkan hasil dan minat belajar matematika - Mumpuni, Panca Wahyu; Inganah , Siti; Sugiarti, Wiwik (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2020)
This classroom action research was motivating by the minimal percentage of class classical completeness, so that the difficulty in understanding the material or interest in learning mathematics is still low. Efforts to overcome those problems through new innovations in managing the classroom to increase interest in learning, so that it was expecting to affect better learning outcomes. Classroom management cannot be separated from the learning model applied. Window shopping learning model is one of the factors of the power of interest in learning. The study consisted of two cycles with the same stages, namely planning, implementing, observing, and reflecting. This study shows an increase in interest in learning in the high category with details of Cycle I of 77% and Cycle of 81%. Improve student learning outcomes with criteria of more than 75%. Learning outcomes from the results of data analysis obtained 66% Cycle I and 77% Cycle II. The results showed that the window shopping learning model could increase the interest and learning outcomes of students at SMA Negeri 2 Batu, especially in vector material.